Akuntabilitas Keuangan dan Kompetensi Aparatur Sipil Negera Terhadap Akuntabilitas Kinerja Dinas Perdagangan Perindustrian Kota Pekanbaru - Fachroh Fiddin (Magister Manajemen STIE Bank BPD Jateng, 2021)
This study aims to analyze and examine the effect of the application of financial accountability and employee competence on the performance accountability of government agencies at the Pekanbaru City Trade and Industry Office. The research respondents of this study were all civil servants at the Pekanbaru City Trade and Industry Office. The data used in this study were obtained from individual perceptions regarding the application of financial accountability, employee competence and accountability for the performance of government agencies in the Department of Trade and Industry in Pekanbaru City. The data obtained after distributing the questionnaire were 81 people. Data analysis using multiple regression techniques supported by secondary data. The results showed that the application of financial accountability had no effect on the accountability of the performance of government agencies and the competence of employees either simultaneously or partially had an effect on the accountability of the performance of government agencies.